Enhanced efficiency fertilisers: a review of formulation and nutrient release patterns. (12th August 2014) - Timilsena, Yakindra Prasad; Adhikari, Raju; Casey, Phil; Muster, Tim; Gill, Harsharn; Adhikari, Benu
Abstract Fertilisers are one of the most important elements of modern agriculture. The application of fertilisers in agricultural practices has markedly increased the production of food, feed, fuel, fibre and other plant products. However, a significant portion of nutrients applied in the field is not taken up by plants and is lost through leaching, volatilisation, nitrification, or other means. Such a loss increases the cost of fertiliser and severely pollutes the environment. To alleviate these problems, enhanced efficiency fertilisers (EEFs) are produced and used in the form of controlled release fertilisers and nitrification/urease inhibitors. The application of biopolymers for coating in EEFs, tailoring the release pattern of nutrients to closely match the growth requirement of plants and development of realistic models to predict the release pattern of common nutrients have been the foci of fertiliser research. In this context, this paper intends to review relevant aspects of new developments in fertiliser production and use, agronomic, economic and environmental drives for enhanced efficiency fertilisers and their formulation process and the nutrient release behaviour. Application of biopolymers and complex coacervation technique for nutrient encapsulation is also explored as a promising technology to produce EEFs. © 2014 Society of Chemical Industry